2015
DOI: 10.2298/jsc141218030f
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent effect of difenoconazole on enzymatic activity from the soil

Abstract: The purpose of this study was to quantify the effect of difenoconazole (DFC) on the activity of a few enzymes commonly found on soil: dehydrogenase, urease, phosphatase and protease. Three experimental variants were established: in field conditions with variable temperature (10-21 ?C, variants A1-A3), under laboratory conditions with constant temperature (30 ?C, variants B1-B3) and untreated soil (C variant). The commercial product "Score 250EC" with 250 g DFC L-1 was used at the following co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…Literature data reveal the stimulation or inhibition of the enzymes' activities in the presence of herbicides, depending on the type of the herbicide, its dose, the incubation temperature, application interval, inorganic and organic soil content, soil type, soil maintenance works, heavy metal content and other environmental factors [15][16][17][18][19][20]. Soil temperature and humidity are two factors that reduce the herbicides toxicity and their persistence in soil [19,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Literature data reveal the stimulation or inhibition of the enzymes' activities in the presence of herbicides, depending on the type of the herbicide, its dose, the incubation temperature, application interval, inorganic and organic soil content, soil type, soil maintenance works, heavy metal content and other environmental factors [15][16][17][18][19][20]. Soil temperature and humidity are two factors that reduce the herbicides toxicity and their persistence in soil [19,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Temperature has already proven to influence the action of fungicides such as difenoconazole, as confirmed by Filimon et al (2015), who detected a lower enzymatic activity of the soil microbiota when exposed to difenoconazole at higher temperatures. Temperature also influenced the rate of dissipation of these compounds in natural soils, as tested by Guo et al (2010), Castillo and Torstensson (2007) and Fenoll et al (2009), supporting our results, especially from tests at higher temperatures.…”
Section: Figmentioning
confidence: 73%
“…Several previous studies investigated the effects of difenoconazole (DFC) on soil bacterial communities, such as its biodegradation, the dehydrogenase and dimethylsulfoxid activities in soils, along with a certain fraction of microflora that not only became resistant to this product, but metabolized it as well. Other studies investigated the effects of DFC on dehydrogenase, phosphatase, urease and protease activities within soils and found a decreasing activity, but also an increased activity of protease at concentrations of 0.150 mg DFC / g soil [17]. It was equally showed that the DFC residues in rice plants (recorded within safe limits for human consumption) and in paddy soils (below the detection limit <0.01 mg/kg) [18].…”
Section: Abstract: Difenoconazole Soil Bacteriamentioning
confidence: 99%
“…Previous investigations regarding the effects of DFC on soil communities were undertaken using biochemical analyses (e.g. enzymes), underlining the indirect effects of this fungicide on these communities [14,17,20].…”
Section: Abstract: Difenoconazole Soil Bacteriamentioning
confidence: 99%